Hubungan Antara Pembiasaan Profil Pelajar Pancasila dengan Peningkatan Karakter Disiplin dan Prestasi Akademik Siswa Sekolah Dasar : Systematic Literature Review - Nisrina, Ajeng Nida; Rosmilawati, Ila; Juansah, Dase Erwin (LPPM Universitas Bina Bangsa, 2025)
The transformation of education in Indonesia through the Merdeka Curriculum emphasizes the strengthening of student character by internalizing the values of the Pancasila Student Profile. Among these values, discipline plays a crucial role in supporting students’ academic success, especially at the elementary school level. This study aims to explore the relationship between the habituation of Pancasila Student Profile values, the development of disciplined character, and students’ academic performance. A Systematic Literature Review (SLR) method was employed, utilizing the PRISMA protocol to identify and analyze articles from four major academic databases: Google Scholar, SINTA, Garuda, and DOAJ. Articles were selected based on inclusion criteria such as relevance to the elementary school context, connection to the studied variables, and publication between 2018 and 2024. The findings reveal that consistent practice of Pancasila values contributes positively to students’ character development, particularly in fostering discipline, which in turn supports improved academic outcomes. These insights highlight the importance of embedding character education within daily learning activities and suggest the need for more structured policy implementation in elementary education settings.